Legal Protection Of Surgical Doctors That Does The Operation In Palembang Charitas Group Hospital - Febrero Andro Dwi Fauzan; Helwan Kasra (Universitas Muhammadiyah Sumatera Utara, 2023)
The formulation of the problem in this study is 1) What is the legal protection for surgeons in carrying out operations that result in patients dying at Charitas Group Hospital Palembang? and 2) What are the factors that influence the legal protection of surgeons in carrying out operations that result in the patient's death at Charitas Group Hospital Palembang?. The research method used is normative and empirical juridical research. Sources of data used in this study consist of primary data and secondary data. Based on the results of the study, it shows that 1) Legal protection for surgeons who carry out operations at the Charitas Group Hospital in Palembang is carried out in a preventive and repressive manner because until now doctors in the city of Palembang have received fairly good legal protection, even though doctors on duty also often receive complaints from the patient or the patient's family because civilly it can be resolved through mediation where legal protection for the surgeon who performs surgery will be accepted if the obligations inherent in a medical profession are fulfilled in Law no. . 36 of 2009 concerning Health. Law No. 29 of 2004 concerning Medical Practice, Government Regulation No. 32 of 1996 concerning Health Workers, and Law no. 36 of 2014 concerning Health Workers and Hospitals are also responsible for malpractice lawsuits according to article 46 of the Hospital Act.; and 2) s family because civilly it can be resolved through mediation where legal protection for the surgeon who performs surgery will be accepted if the obligations inherent in a medical profession are fulfilled in Law no. 36 of 2009 concerning Health. Law No. 29 of 2004 concerning Medical Practice, Government Regulation No. 32 of 1996 concerning Health Workers, and Law no. 36 of 2014 concerning Health Workers and Hospitals are also responsible for malpractice lawsuits according to article 46 of the Hospital Act.; and 2) s family because civilly it can be resolved through mediation where legal protection for the surgeon who performs surgery will be accepted if the obligations inherent in a medical profession are fulfilled in Law no. 36 of 2009 concerning Health. Law No. 29 of 2004 concerning Medical Practice, Government Regulation No. 32 of 1996 concerning Health Workers, and Law no. 36 of 2014 concerning Health Workers and Hospitals are also responsible for malpractice lawsuits according to article 46 of the Hospital Act.; and 2)Factors that affect legal protection for surgeons in carrying out operations include SOP violations, clinical pathway incompatibility, informed consent and medical ethics in serving patients